(untitled) (Panacea Journal of Medical Sciences, 2025)
Pancytopenia is a medical condition where there is decrease in cell count from all three lineages from bone marrow resulting in anaemia, leukopenia, and thrombocytopenia. It is usually due to the underlying disease process affecting bone marrow or peripheral blood cells. To study patients suffering from pancytopenia and evaluate clinical presentation, haematological & biochemical features, complications, and outcome of the patients. The present study was a prospective observational study. In a series of 6 pancytopenia cases, we found a case of each of methotrexate overdose, vitamin B12 deficiency, complicated vivax malaria, fungal infection, myelodysplastic syndrome, hypoplastic anaemia. We observed different spectrum of presentation, clinical course, complications, response to treatment and outcome of all the cases of pancytopenia.